2018
DOI: 10.1111/jne.12660
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐ and sub region‐dependent modulation of arcuate kisspeptin neurones by vasopressin and vasoactive intestinal peptide

Abstract: A population of kisspeptin neurones located in the hypothalamic arcuate nucleus (ARN) very likely represent the gonadotrophin‐releasing hormone pulse generator responsible for driving pulsatile luteinising hormone secretion in mammals. As such, it has become important to understand the neural inputs that modulate the activity of ARN kisspeptin (ARNKISS) neurones. Using a transgenic GCaMP6 mouse model allowing the intracellular calcium levels ([Ca2+]i) of individual ARNKISS neurones to be assessed simultaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Acute brain slices were prepared from adult male Kiss1::GCaMP6 mice in which 90%‐95% of ARN KISS neurones display robust NKB‐evoked increases in GCaMP6 fluorescence in ARN KISS neurones (Figure 4A). 18 Using the two‐stimulation NKB protocol, the second NKB‐evoked elevation in [Ca] i was found to be higher than the first, generating an S2/S1 of 1.09 ± 0.09 (Figure 4B). Inclusion of 100 nmol L ‐1 NPY at the same time as the second NKB stimulus generated a marked decrease in evoked [Ca] i rise, with the resultant S2/S1 being 0.20 ± 0.05 (n = 30 from three mice; P < 0.001, Wilcoxon signed rank test) (Figure 4).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Acute brain slices were prepared from adult male Kiss1::GCaMP6 mice in which 90%‐95% of ARN KISS neurones display robust NKB‐evoked increases in GCaMP6 fluorescence in ARN KISS neurones (Figure 4A). 18 Using the two‐stimulation NKB protocol, the second NKB‐evoked elevation in [Ca] i was found to be higher than the first, generating an S2/S1 of 1.09 ± 0.09 (Figure 4B). Inclusion of 100 nmol L ‐1 NPY at the same time as the second NKB stimulus generated a marked decrease in evoked [Ca] i rise, with the resultant S2/S1 being 0.20 ± 0.05 (n = 30 from three mice; P < 0.001, Wilcoxon signed rank test) (Figure 4).…”
Section: Resultsmentioning
confidence: 93%
“…Experiments were performed in the presence of tetrodotoxin and a cocktail of amino acid receptor antagonists to block any indirect actions of NPY. Although we used 50 nmol L ‐1 NKB in the electrophysiological studies, 100 nmol L ‐1 NKB is found to provide a more consistent stimulation in calcium imaging investigations 18 . Acute brain slices were prepared from adult male Kiss1::GCaMP6 mice in which 90%‐95% of ARN KISS neurones display robust NKB‐evoked increases in GCaMP6 fluorescence in ARN KISS neurones (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To modulate the balance of negative and positive E2 feedback, the SCN coordinates the activity of two opposing ERα-expressing neuropeptidergic systems that lie upstream of the GnRH system: the stimulatory neuropeptide, kisspeptin, and the inhibitory neuropeptide, RFamide-related peptide-3 (RFRP-3; the mammalian orthologue of avian gonadotrophin-inhibitory hormone [GnIH]). 4,11,18,[23][24][25][26][27][28][29][30] The SCN coordinates cellular activity of RFRP-3 neurones to suppress the reproductive axis outside the time window of the LH surge and to allow for the transient suppression of E 2 -negative-feedback around the time of the LH surge. 11,18,23 RFRP-3 neurones are concentrated in the dorsomedial hypothalamus (DMH) and project broadly to hypothalamic loci that contain GnRH neurones and fibres (ie, medial septum, diagonal band of Broca, preoptic area, anterior hypothalamus and arcuate nucleus [ARC]) in addition to the ventromedial nucleus of the hypothalamus and brainstem.…”
mentioning
confidence: 99%